Analisis Borepile Menggunakan Metode Meyyerhoff dan Reese Wright - Lydia Darmiyanti; Yonas Prima; Muhammad Arief Aldianto (Jurnal Sipil Krisna, 2023)
Given that the project site is in a highly populated area and has a geological condition of soil with a relatively high water content, the borepile foundation is the best option. The purpose of this study is to compare settlement estimates made manually and using the Plaxis 3D application, as well as to examine the bearing capability of the borepile foundation utilizing sondir data and conventional penetration tests. The research methodology used to write this final project was a case study, and it involved observation as the primary data collection tool. Using the Mayerhoff method, the following values were determined for the borepile bearing capacity: Qult = 152.403 tons, Qijin = 32.15527, Qtotal = 718.4571, and Qijin = 160.4381. and for SPT data using the Reese & Wright method at borepile point A18 obtained Qu = 1163.89 tons, and Qijin = 387.964 tons. In the manual method of the semi-empirical method and the vesic method for the analysis of the single borepile drop at point A18, S =15 mm and S = 12.8 mm, respectively. The output of the Plaxis 3D program is S = 19.2 mm, and the PDA test results are achieved. S = 5mm. The results of the settlement analysis, which was performed, have complied with SNI 8460: 2017's standards for foundation settlement, which is 25 mm.